2011
DOI: 10.2209/tdcpublication.52.155
|View full text |Cite
|
Sign up to set email alerts
|

Number of Occlusal Units Estimated from Number of Present Teeth

Abstract: The aim of this study was to determine the relationship between number of present teeth (PT) and number of occlusal units (OUs). The data were obtained from a periodontal disease examination based on the health promotion law in Tokyo, Japan in 2005. Data from a total of 1,549 (524 male and 1,025 female) 60-year-old people were analyzed in this study. The number of OUs was counted by analyzing their dental charts. Any pair of opposing teeth of the same type was counted as one OU. The maximum number of OUs in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…The WHO stated in 1992 that throughout life, the retention of a functional, aesthetic, natural dentition of 20 teeth, without prosthesis, should be the treatment goal for oral health 30) . The mean number of occlusal pairs among molars changes from 2 or more pairs to less than 2 pairs at the cut-off point between 26 and 25 PT 34) .…”
Section: Present Teeth Groupsmentioning
confidence: 99%
“…The WHO stated in 1992 that throughout life, the retention of a functional, aesthetic, natural dentition of 20 teeth, without prosthesis, should be the treatment goal for oral health 30) . The mean number of occlusal pairs among molars changes from 2 or more pairs to less than 2 pairs at the cut-off point between 26 and 25 PT 34) .…”
Section: Present Teeth Groupsmentioning
confidence: 99%
“…In previous reports, we showed that there is likely to be a direct relationship between the number of PT and OPs 23) . In the report, we can be estimated OPs from the number of PT.…”
Section: Introductionmentioning
confidence: 64%
“…The data of OPs, as in our previous reports 22,23) , were based on a periodontal disease examination carried out under a health promotion law in a city located northeast of Tokyo, Japan, in 2005. Data from a total of 5,156 (1,745 male and 3,411 female) 40, 50 and 60-year-old participants were analysed.…”
Section: Determining the Values Of Pt To Opsmentioning
confidence: 99%
“…During their survival period, transplanted teeth ease the masticatory burden on other teeth. Yoshino et al 19) reported on the relationship between number of PT and OPs, finding that the mean number of OPs was 10.4 at 24 PT and 7.2 at 20 PT. These reports and the results of the current study indicate that the cut-off point for deciding between implants and dentures should be around 20 PT.…”
Section: )mentioning
confidence: 99%